2017
DOI: 10.1016/s0140-6736(17)31368-5
|View full text |Cite
|
Sign up to set email alerts
|

Infection-related microcephaly after the 2015 and 2016 Zika virus outbreaks in Brazil: a surveillance-based analysis

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
233
4
33

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(280 citation statements)
references
References 21 publications
10
233
4
33
Order By: Relevance
“…It is also tempting to speculate that the 2015/2016 imbalance in reporting may have been a general phenomenon across Brazil. As described elsewhere, it is thus possible that FSA is a good example of states and urban centres that may have witnessed larger epidemics than reported in 2015 (de Oliveira et al, 2017). This, together with our conclusion that low MC risk with very high attack rates makes ZIKV a public health concern, could explain why most MC reports at the level of the country were in 2015 (de Oliveira et al, 2017), although for many regions the total reported number of ZIKV cases may have been surprisingly small that year.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is also tempting to speculate that the 2015/2016 imbalance in reporting may have been a general phenomenon across Brazil. As described elsewhere, it is thus possible that FSA is a good example of states and urban centres that may have witnessed larger epidemics than reported in 2015 (de Oliveira et al, 2017). This, together with our conclusion that low MC risk with very high attack rates makes ZIKV a public health concern, could explain why most MC reports at the level of the country were in 2015 (de Oliveira et al, 2017), although for many regions the total reported number of ZIKV cases may have been surprisingly small that year.…”
Section: Discussionmentioning
confidence: 93%
“…The rise in ZIKV incidence in FSA coincided temporally with an increase in cases of Guillain-Barré syndrome (GBS) and microcephaly (Faria et al, 2016a), with an unprecedented total of 21 confirmed cases of microcephaly in FSA between January 2015 and May 2017. There is wide statistical support for a causal link between ZIKV and severe manifestations such as microcephaly (Rubin et al, 2016; de Araújo et al, 2016; Soares de Araújo et al, 2016; Honein et al, 2017; Brasil et al, 2016; de Oliveira et al, 2017), and the proposed link in 2015 led to the declaration of the South American epidemic as an international public health emergency by the World Health Organization (WHO) in 2016; the response to which has been limited to vector control initiatives and advice to delay pregnancy in the affected countries (WHO, 2016b; WHO, 2016a). With few cohort studies published (Honein et al, 2017; Brasil et al, 2016) and the lack of an established experimental model for ZIKV infection (Aman and Kashanchi, 2016; Dowall et al, 2016), modelling efforts have taken a central role for advancing our understanding of the virus’s epidemiology (Chowell et al, 2016; Ferguson et al, 2016; Bogoch et al, 2016; Nishiura et al, 2016; Zhang et al, 2016; Perkins et al, 2016; Messina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, ZIKV was declared a Public Health Emergency after researchers reported an unexpected increase in the diagnosis of fetal and pediatric microcephaly [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the sudden rise in congenital abnormalities and occurrences of Guillain-Barré syndrome, the scientific community established a causal association between ZIKV infection and these neurological adverse outcomes 79 . This led the WHO to declare ZIKV and its suspected link to birth defects 10,11 a Public Health Emergency of International Concern in February 201612.…”
Section: Introductionmentioning
confidence: 99%